2021
DOI: 10.1108/apjba-07-2020-0252
|View full text |Cite
|
Sign up to set email alerts
|

Moderation effect of social support and personal resources between emotional work and employee wellbeing

Abstract: PurposeThere is dearth of studies in the literature which have discussed the relevance of personal and social resources of employees to protect them from adverse impacts of emotional job demands. However, interaction effect of these two resources on wellbeing of the employees in context to emotional work is inadequate. The present study is aimed to address the existing gap and investigate the relevance of personal and social resources as moderators in the presence of each other between emotional work and emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 99 publications
1
4
0
1
Order By: Relevance
“…Buffering roles of meaningful work in counseling trainees have not been addressed thus far to our best knowledge. Nevertheless, our findings are aligned with some studies that identified personal resources as buffering moderators in the relationship between risk factors and outcomes (e.g., Cheung et al., 2019; Mehta & Sharma, 2021), given that meaningful work is considered a crucial personal resource (Benitez et al., 2023; Meng et al., 2023). Our findings showed that the higher the meaningful work of counseling trainees, the weaker the negative relationship between their academic burnout and career choice satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Buffering roles of meaningful work in counseling trainees have not been addressed thus far to our best knowledge. Nevertheless, our findings are aligned with some studies that identified personal resources as buffering moderators in the relationship between risk factors and outcomes (e.g., Cheung et al., 2019; Mehta & Sharma, 2021), given that meaningful work is considered a crucial personal resource (Benitez et al., 2023; Meng et al., 2023). Our findings showed that the higher the meaningful work of counseling trainees, the weaker the negative relationship between their academic burnout and career choice satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Past empirical studies have reported the beneficial effect of HCN coworker support on work adjustment (Bader, 2017), which is less likely to make expatriates exhausted. The perception or actual availability of HCN coworker support may enhance expatriates' feeling of being accepted and promote their confidence in expending effort toward the completion of assignments (Mart ınez, 2017; Mehta and Sharma, 2021). Because COR theory identifies social support to be functional in handling stress (Charoensukmongkol and Phungsoonthorn, 2020), this study postulates a negative linkage between HCN coworker support and burnout.…”
Section: Mediating Effect Of Hcn Coworker Supportmentioning
confidence: 94%
“…Dienhart et al (1992) have observed that employees with service orientation tend to be observant, agreeable, polite and receptive to customers' requirements. Likewise, a few studies have defined service orientation as a degree to which service firm employees operate in a non-conventional way to resolve customer issues and show commitment with a lot of integrity to provide excellent services to satisfy customers' needs (Frimpong and Wilson, 2013;Mehta and Sharma, 2021). Subsequently, preceding studies have defined that service orientation in service recovery is operationalized as the attitude and behavior of employees, which may transform Impact of service recovery antecedents customers' experience positively (Li and Huang, 2017;Popli and Rizvi, 2015).…”
Section: Customer Service Orientation and Customer Satisfactionmentioning
confidence: 99%